Orthogonal gap-enhanced Raman tags for interference-free and ultrastable surface-enhanced Raman scattering - Li Jin; Liu Fugang; He Chang; Shen Feng; Ye Jian (Nanophotonics)
Spectral interference from backgrounds is not negligible for surface-enhanced Raman scattering (SERS) tags and often influences the accuracy and reliability of SERS applications. We report the design and synthesis of orthogonal gap-enhanced Raman tags (O-GERTs) by embedding alkyne and deuterium-based reporters in the interior metallic nanogaps of core–shell nanoparticles and explore their signal orthogonality as optical probes against different backgrounds from common substrates and media (e.g., glass and polymer) to related targets (e.g., bacteria, cancer cells, and tissues). Proof-of-concept experiments show that the O-GERT signals in the fingerprint region (200–1800 cm−1) are likely interfered by various backgrounds, leading to difficulty of accurate quantification, while the silent-region (1800–2800 cm−1) signals are completely interference-free. Moreover, O-GERTs show much higher photo and biological stability compared to conventional SERS tags. This work not only demonstrates O-GERTs as universal optical tags for accurate and reliable detection onto various substrates and in complex media, but also opens new opportunities in a variety of frontier applications, such as three-dimensional data storage and security labeling.